2013
DOI: 10.4103/1319-2442.118082
|View full text |Cite
|
Sign up to set email alerts
|

Relation of middle molecules levels and oxidative stress to erythropoietin requirements in high-flux versus low-flux hemodialysis

Abstract: The objective of this study is to investigate the serum beta-2-microglobulin (B2MG) and advanced oxidation protein products (AOPP) as middle molecule uremic toxins and protein carbonyl (PCO) as oxidative stress marker in uremic patients undergoing high-flux versus low-flux hemodialysis (HD) and to correlate their levels to the erythropoietin requirements for those patients. Twenty patients on chronic low-flux HD were recruited in the study. At the start of the study, all patients underwent high-flux HD for eig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Similar to the present study, there have been reports that AOPP levels are decreased by dialysis, while other reports have indicated that dialysis increases AOPP levels by inducing protein damage via reactive oxygen species. [40][41][42] Therefore, further studies are warranted. The vitamin E-coated membrane also exhibited reduced fibrinogen adhesion on POD 1.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to the present study, there have been reports that AOPP levels are decreased by dialysis, while other reports have indicated that dialysis increases AOPP levels by inducing protein damage via reactive oxygen species. [40][41][42] Therefore, further studies are warranted. The vitamin E-coated membrane also exhibited reduced fibrinogen adhesion on POD 1.…”
Section: Discussionmentioning
confidence: 99%
“…High-flux dialysis may improve patient hemoglobin levels through improved clearance of moderate- and high-molecular-weight toxins [ 40 ]. The average weekly dose of human recombinant erythropoietin required to maintain target hemoglobin levels on high-flux dialysis is lower than the average dose needed in patients on low-flow dialysis [ 41 ]. In addition, a randomized prospective study revealed that patients on high-flux dialysis had a significantly greater rate of goal Hb attainment than did those in the low-flux group, and high-flux dialysis was beneficial for maintaining stable hemoglobin levels [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The last group of toxins consists of middle molecules. Similar to the previous groups, they may cause various biochemical and metabolic disorders, which will intensify the inflammation and damage the blood vessel wall [20]. Glorieux et al [21] investigated the serum beta2-microglobulin (B2MG) and advanced oxidation protein products (AOPP) as middle molecule uremic toxins and protein carbonyl (PCO) as oxidative stress marker in uremic patients undergoing high-flux versus low-flux hemodialysis (HD).…”
Section: Uremic Toxins and Ckdmentioning
confidence: 91%